Models and methods for analyzing DCE‐MRI: A review. Issue 12 (17th November 2014) - Khalifa, Fahmi; Soliman, Ahmed; El‐Baz, Ayman; Abou El‐Ghar, Mohamed; El‐Diasty, Tarek; Gimel'farb, Georgy; Ouseph, Rosemary; Dwyer, Amy C.
Abstract : Purpose: To present a review of most commonly used techniques to analyze dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI), discusses their strengths and weaknesses, and outlines recent clinical applications of findings from these approaches. Methods: DCE‐MRI allows for noninvasive quantitative analysis of contrast agent (CA) transient in soft tissues. Thus, it is an important and well‐established tool to reveal microvasculature and perfusion in various clinical applications. In the last three decades, a host of nonparametric and parametric models and methods have been developed in order to quantify the CA's perfusion into tissue and estimate perfusion‐related parameters (indexes) from signal‐ or concentration–time curves. These indexes are widely used in various clinical applications for the detection, characterization, and therapy monitoring of different diseases. Results: Promising theoretical findings and experimental results for the reviewed models and techniques in a variety of clinical applications suggest that DCE‐MRI is a clinically relevant imaging modality, which can be used for early diagnosis of different diseases, such as breast and prostate cancer, renal rejection, and liver tumors. Conclusions: Both nonparametric and parametric approaches for DCE‐MRI analysis possess the ability to quantify tissue perfusion.